(untitled) - Green-Biomass Research Group in Graduate School of Agriculture at TUAT ([Tokyo], 2009)
This project aims to establish the research infrastructure of green biomass in Asia. Green biomass is expected to establish the self-sustaining local energy system by using various bioresources, climate and natural features, agricultural production technologies and rural society which are created and subsisted in Asis
Keywords: Nguồn năng lượng có thể tái tạo,Năng lương sinh khối,Renewable energy sources,Biomass energy